Pengaruh E-Service Quality dan Trust Terhadap Keputusan Pembelian Jasa Kamar di Platform Traveloka pada Hotel Bintang 3 di Kota Padang - Ummah, Kuntum Khaira; Adrian, Arif; Abrian, Youmil (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2023)
Based on data from Traveloka in booking rooms at 3 Star Hotels in Padang City, there was instability reservation from December 2022 to June 2023 and there was also customer dissatisfaction with customers who made online room reservations which caused a lack of customer trust in Traveloka. This research aims to analyze the influence of e-service quality and trust on the decision to purchase a room at Traveloka (study of a 3-star hotel in Padang City). The type of research that the author conducted was quantitative using an associative approach, this was used to determine the influence of E-Service Quality (X1), Trust (X2), on Purchasing Decisions (Y). The population of this research is Traveloka customers who make room reservations via the Traveloka Site at 3 Star Hotels in Padang City. The sample for this research consisted of 350 respondents and used a sampling technique, namely a non-probability sampling technique using purposive sampling. The independent variables examined in this research are E-Quality Service and Trust for the dependent variable, namely Purchase Decisions using PLS-SEM analysis techniques and data descriptions. The results of this research show that the E-Quality Service and Trust variables have a positive effect on purchasing decisions.